The Connection of Pedagogical and Information Communication Technologies in the Modern Training of Future Teachers of the Korean Language - Men Svetlana Rodionovna (Researchparks Publishing, 2023)
Digital transformation in education, namely the use of modern technologies to improve the quality of university education, is determined by the optimization of teacher-student interaction, which leads to the progressive movement of the educational process towards the development of self-sufficient personality for self-education and independent solution of cognitive problems arising at the same time, able to quickly and independently acquire knowledge and critically comprehend them.